2016
DOI: 10.19173/irrodl.v17i1.2113
|View full text |Cite
|
Sign up to set email alerts
|

Does Navigation Always Predict Performance? Effects of Navigation on Digital Reading are Moderated by Comprehension Skills

Abstract: This study investigated interactive effects of navigation and offline comprehension skill on digital reading performance. As indicators of navigation, relevant page selection and irrelevant page selection were considered. In 533 Spanish high school students aged 11-17 positive effects of offline comprehension skill and relevant page selection on digital reading performance were found, while irrelevant page selection had a negative effect. In addition, an interaction between relevant page selection and offline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
1
21
0
3
Order By: Relevance
“…In sum, previous research suggest that good comprehenders in the print medium are more efficient changing from scanning to deep processing whenever they detect a hypertext section relevant for their goal (Coiro & Dobler, ; Zhang & Duke, ), and as a consequence, their comprehension of the hypertext improves (Naumann, Richter, Christmann & Groeben, ; Naumann & Salmerón, ). Nevertheless, those results should be taken cautiously, because previous studies have mostly focused on undergraduate students or on adolescents with high reading comprehension skills.…”
Section: Scanning and Deep Processing Of Information In Hypertext: Anmentioning
confidence: 94%
“…In sum, previous research suggest that good comprehenders in the print medium are more efficient changing from scanning to deep processing whenever they detect a hypertext section relevant for their goal (Coiro & Dobler, ; Zhang & Duke, ), and as a consequence, their comprehension of the hypertext improves (Naumann, Richter, Christmann & Groeben, ; Naumann & Salmerón, ). Nevertheless, those results should be taken cautiously, because previous studies have mostly focused on undergraduate students or on adolescents with high reading comprehension skills.…”
Section: Scanning and Deep Processing Of Information In Hypertext: Anmentioning
confidence: 94%
“…Second, reading skills have been related to the use of link selection strategies in sixth graders (Salmerón & García, ). Reading comprehension was found to be related to reading performance during a Web assignment in high school children, but only for those who selected relevant pages (Naumann & Salmerón, ). Third, although working memory capacity has not directly been related to navigation activities, a related learner characteristic called sustained attention has.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified how proficiently students navigate is a strong predictor of their learning and performance when reading digital texts (Naumann & Salmerón, 2016;Hahnel, et al, 2016). Furthermore, it seems likely that attitudes towards ICT and digital reading proficiency have a reciprocal relation, as has been claimed for reading engagement and print reading proficiency (Guo, et al, 2015;OECD, 2015).…”
Section: Spanish Teenager Digital Contextmentioning
confidence: 93%
“…It is therefore crucial to understand and assess the new forms of reading literacy that come with the practice of reading on digital displays (Naumann, 2008;Coiro, 2009;McEneaney et al, 2009;Vázquez-Cano, Mengual-Andrés, & Roig-Vila, 2015).Therefore, digital reading is involved in a great variety of social and personal activities and situations; for this reason, digital texts need a change in methodological approaches in order to improve the competence of digital reading of students (Rouet, 2006;Kennedy et al, 2008;Kemp, 2011;Coe & Oakhill, 2011). Recent studies have identifi ed how profi ciently students navigate is a strong predictor of their learning and performance when reading digital texts (Naumann & Salmerón, 2016;Hahnel et al, 2016). Furthermore, it seems likely that attitudes towards ICT and digital reading profi ciency have a reciprocal relation, as has been claimed for reading engagement and print reading profi ciency (Guo et al, 2015;OECD, 2015).…”
Section: New Technologies For Text New Ways Of Readingmentioning
confidence: 99%